Optical and structural properties of GaAsBi and InGaBiAs nanostructured semiconductors grown by Molecular Beam Epitaxy - Alghamdi, Haifa (2020)
This thesis investigates the optical and structural properties of GaAs1-xBix/GaAs SQWs and InGaBiAs QDs grown on the conventional (100) and non-conventional (311)B GaAs substrates by Molecular Beam Epitaxy (MBE).